Effect of aging on the stability of ceramic foams prepared by thermostimulated sol-gel process - Santos, E. P.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Kluwer Academic Publ, 2003)
This work presents a new route of preparation of zirconium ceramic foams based on the thermostimulated sol-gel process. This method produces gelled bodies with up to 90% of porosity in the wet gel and can be used to make complex-shaped components. Unfortunately, the shrinkage during the drying step allows to a catastrophic reduction (50%) of the foam porosity. To improve the foam stability we carried out a systematic study of the effect of gel foam aging on the drying process. Samples were aged in closed vessel at 25 C during different time period (from 6 to 240 h). The shrinkage and the mass loss during drying at 50 C were measured in situ, using a non-contact technique performed with a special apparatus. The results show that the total linear shrinkage decreases from 46% to 8% as the aging period increase from 6 to 240 h. This behavior is followed by a small change of total mass loss, from 42 to 54%. It indicates that by aging the structural stiffness of the foams increases due to secondary condensation reactions. Thus, by controlling the aging period, the porosity can be increased from 67 to 75% and the average size of mesopores of dried foams can be screened from 0.3 to 0.9 mum. Finally, these results demonstrate that the thermostimulated sol-gel transition provides a potential route to ceramic foams manufacture.
Keywords: ceramic foams; zirconia; sol-gel; aging and drying process